Exploring the full replacement of cement with expanded polystyrene (EPS) waste in mortars used for masonry construction. (30th August 2020) - Milling, Amrita; Mwasha, Abrahams; Martin, Hector
Highlights: Recycled expanded polystyrene (EPS) waste to reduce carbon footprint and embodied energy in the construction industry. EPS, acetone, and sand mortar exceeds the bond strength characteristics of conventional cement mortars. Cement and water are totally replaced in the construction process. Abstract: Replacing cement which has a high carbon footprint and high embodied energy contributes to a reduction in both energy consumption and greenhouse gas emission. Expanded polystyrene (EPS) is explored as a replacement for cement in conventional based mortars used in joining masonry units. Five (5) mixes of EPS mortar made from EPS beads dissolved in acetone and sharp sand were prepared and the optimum mix was determined and compared to ordinary Portland cement mortar. The results showed that the bond strength of EPS mortars exceeds twice that of cement mortar and that both mortars performed equally on water permeability, and water absorption. Despite being outperformed by cement mortar on compressive strength, tensile strength, and flexural strength, the EPS mortar has the potential of replacing conventional mortars that are currently being used for all empirical masonry design, for general purpose, reinforced interior/above grade exterior, and non-load bearing applications with limited exterior use. EPS products disposal is a global environmental issue and use of the EPS mortar provides an energy credit to the construction industry. This research not only provides an environmentally friendly, non-energy intensive, sustainable alternative to cement-based mortars but it also provides a recycling solution for non-biodegradable voluminous EPS waste.